Palliative practices : an interdisciplinary approach - Kuebler, Kim K. 4 0 16; Davis, Mellar P.;Moore, Crystal Dea.; 5 (St. Louis, Missouri : Elsevier Mosby, 2005)
The first book of its kind to examine the integration of palliative interventions from a disease-specific approach
Unit I. Issues specific to palliative care. Palliative care perspectives / Barry M. Kinzbrunner -- Advance care planning / Crystal Dea Moore -- Evidence-based interventions / Dana N. Rutledge -- Pharmacology / Mellar P. Davis -- The interface of sleep / Kathy P. Parker -- Unit II. Specific disease states and symptom management. Cardiovascular / Nancy M. Albert -- Pulmonary / James Varga, Josua Cox -- Nephrology / Michael Germain, Lewis M. Cohen -- Oncology / Mary Magee Gullatte, Roberta Kaplow, Debra E. Heidrich -- Cancer pain / Mellar P. Davis, Jan L. Frandsen -- Neurology / Mellar P. Davis ... [et al.] -- Unit III. The dying process, grief, and bereavement. Ethical issues / Tom Tomlinson -- Cultural and spiritual issues / Diane B. Loseth ... [et al.] -- The dying process / Catherine Vena, Kim Kuebler, Sandra E. Schrader -- Grief and bereavement / Helen Kathleen Brophy McHale -- Appendixes. Medications by disorder / Kim Kuebler, James Varga, Mellar P. Davis -- Medication routes and metabolism / Kim Kuebler, James Varga, Mellar P. Davis -- Palliative care assessment tools / Marilyn O'Mallon, Kim Kuebler -- Websites / Kim Kuebler.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; methods.;methods.;methods. -- Palliative treatment.;Terminal care.;Palliative Care;Bereavement.;Patient Care Management;Terminal Care;Soins palliatifs.;Soins en phase terminale. -- 20; 20; 2